2019
DOI: 10.1634/theoncologist.2019-0146
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Financial Burden of Cancer Clinical Trial Participation: Longitudinal Effects of an Equity Intervention

Abstract: Financial barriers may discourage some patients with from participating in cancer clinical trials. This study sought to assess the effect of an equity intervention on the financial burden of clinical trial participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 38 publications
(52 reference statements)
5
37
1
Order By: Relevance
“…The median value in our study was 20, indicating worse financial toxicity than that seen in prior studies of patients enrolled in clinical trials, in which the median FTS was 24, and in insured patients with multiple myeloma, in which the median FTS was 23. 13,25 This finding is consistent with a prior study reporting that the prevalence of high financial burden (indicated by COST FTS ≤ 24) was more than two-fold higher among phase I clinical trial patients (67%) than among oncology patients treated with curative-intent surgery (30%). 26 Patients used a variety of means to pay for their clinical trial-related expenses.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The median value in our study was 20, indicating worse financial toxicity than that seen in prior studies of patients enrolled in clinical trials, in which the median FTS was 24, and in insured patients with multiple myeloma, in which the median FTS was 23. 13,25 This finding is consistent with a prior study reporting that the prevalence of high financial burden (indicated by COST FTS ≤ 24) was more than two-fold higher among phase I clinical trial patients (67%) than among oncology patients treated with curative-intent surgery (30%). 26 Patients used a variety of means to pay for their clinical trial-related expenses.…”
Section: Discussionsupporting
confidence: 90%
“…To date, there is limited evidence regarding financial toxicity for patients enrolled in clinical trials, with only one prior study examining the role of an equity intervention for patients with cost concerns. 13 We found that financial toxicity was higher for patients with income ≤$60,000 and for patients who traveled farther to receive their care. These data build on existing knowledge that both of these groups are underrepresented in clinical trials, 5 suggesting that both groups have barriers to entry into clinical trials and additional financial concerns after enrollment.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Many studies have used questions to identify patients with FT that focus on indirect costs of cancer care (eg, travel, lodging, and employment) rather than questions that evaluate the ability of the patient to financially manage their basic needs of living (eg, medicines, food, and clothing), which is more relevant to older adults with limited incomes. 10,15,16 In this secondary analysis of a large national clinical trial, we aimed to (1) estimate the prevalence of FT in older patients with advanced cancer enrolled in a clinical trial, (2) examine the association between FT and HRQoL, and (3) describe cost conversations between oncologists and patients with FT. We hypothesized that FT was associated with worse HRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…ASCO assembled a Cancer Trial Accrual Symposium in 2013, with recommendations in favor of promoting equity in accrual by providing financial support, engaging with patients and providers in minority and/or under-resourced communities, and incentivizing physician involvement. 9 Community-based pilot programs implementing these recommendations have begun operating successfully, 10 and digital media platforms like TheMedNet hold promise in connecting patients and providers to active trials with which they may not otherwise have been familiar.…”
mentioning
confidence: 99%